2021
DOI: 10.3389/fpsyg.2021.644286
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences Facing the COVID-19 Pandemic: The Role of Age, Gender, Personality, and Positive Psychology

Abstract: Research on individual differences in facing the COVID-19 pandemic seems to be crucial in order to design diverse and highly effective intervention strategies. This study uses a sample of 302 North American participants who were recruited through the crowdsourcing platform ProA; different profiles were established, profiling variables of interest in facing the COVID-19 outbreak. Socio-demographic and psychological (personality traits, gratitude, life purpose, and religiosity) variables were explored. These res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
2
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 57 publications
1
35
2
9
Order By: Relevance
“…Other studies provide support to gender differences in the increase of negative emotions due to COVID-19 sudden health and lifestyle changes ( Ahuja et al, 2020 ; Galasso et al, 2020 ; García-Fernández et al, 2021 ; Shockley et al, 2020 ; Bernabe-Valero et al, 2021 ; Kidd et al, 2021 ), although they do not provide a final say on which specific emotion women are more affected than men, and whether the gender difference is driven by that specific emotion or by the fixed effect of a mental state degraded by COVID-19 side-effects. Furthermore, like those of Guadagni et al (2020) and Ausín et al (2021) , these studies focus on at least one of the emotions we included in our survey, although none of them analyze gender effects on sadness, discouragement, nervousness, boredom, emptiness, and stress within the same survey.…”
Section: Research Hypothesesmentioning
confidence: 98%
“…Other studies provide support to gender differences in the increase of negative emotions due to COVID-19 sudden health and lifestyle changes ( Ahuja et al, 2020 ; Galasso et al, 2020 ; García-Fernández et al, 2021 ; Shockley et al, 2020 ; Bernabe-Valero et al, 2021 ; Kidd et al, 2021 ), although they do not provide a final say on which specific emotion women are more affected than men, and whether the gender difference is driven by that specific emotion or by the fixed effect of a mental state degraded by COVID-19 side-effects. Furthermore, like those of Guadagni et al (2020) and Ausín et al (2021) , these studies focus on at least one of the emotions we included in our survey, although none of them analyze gender effects on sadness, discouragement, nervousness, boredom, emptiness, and stress within the same survey.…”
Section: Research Hypothesesmentioning
confidence: 98%
“…One should bear in mind that this measurement is a global judgment that does not consider other processes that are involved in the assessment of emotional state. The fact of making a global judgment in relation to CT has implications in the participant’s categorization in relation to gratitude and affect ( Bernabe-Valero et al, 2021 ). In this way, it was found that participants with poorer affect were more biased when making such global judgments, even when reporting similar values in gratitude.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the authors investigated how this construct is related to moral decisions and response to COVID-19 concluding a positive impact on prosociality. In a previous study, we have found that the four subscales of gratitude (Interpersonal Gratitude, Gratitude in the face of Suffering, Recognition of Gifs, and Expression of Gratitude) were positively associated with positive affect as well as inversely associated with negative affect, indicating that people who are more grateful, both to other people and to transcendental forces, experience a better affective experience ( Bernabe-Valero et al, 2021 ). Moreover, higher scores on gratitude have been also found to be predictors of a lower impact to academic functioning at the end of the semester during the current COVID-19 outbreak ( Bono et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in France, the experience of the COVID-19 pandemic-related school closures differed between households, depending on access to the Internet and computer equipment (Institut National de la Statistique et des Etudes Economiques, 2020 ). Studies from education and social psychology have shown that experiencing long periods of school closure has negative effects on learning, motivation, and psychosocial well-being of the students (Sprang and Silman, 2013 ; Benke et al, 2020a , b ; Dorn et al, 2020 ; Guessoum et al, 2020 ; Magklara et al, 2020 ; UNESCO, 2020 ; Bernabe-Valero et al, 2021 ; Garcia-Esquinas et al, 2021 ; Rajmil et al, 2021 ). Their direct interaction with friends and teachers at school has also been shown to counteract the negative effects of stressful life events on the well-being and mental health of the students (Shahar et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%